Digital marketing strategy through facebook social media to increase sales at Rifki Jaya furniture store Bandar Lampung - Azmir, Arian; Purnomo, Agus (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to explore the impact of digital marketing strategies, specifically through Facebook, on the growth and sustainability of Rifki Jaya Furniture, a company established in 2021. It focuses on the role of market segmentation, customer engagement, and content quality in enhancing product visibility, customer loyalty, and sales. A qualitative approach was employed, analyzing Rifki Jaya Furniture's social media presence and digital marketing tactics on Facebook. The study used data from customer interactions, social media engagement metrics, and content analysis to examine how these factors contribute to the company’s success.  The findings indicate that Rifki Jaya Furniture effectively segments its market by leveraging data from customer interactions on Facebook. Engaging, high-quality content not only captures attention but also fosters trust, which influences consumer purchasing decisions. The company's focus on maintaining strong customer relationships through personalized communication has contributed to increased customer loyalty and repeat sales. Furthermore, the analysis shows that digital marketing on Facebook significantly expanded the company’s market reach and enhanced product visibility. The study concludes that Facebook is an effective tool for small businesses like Rifki Jaya Furniture to strengthen customer relationships, enhance market presence, and drive sales growth. Digital marketing strategies, when executed effectively, can ensure business sustainability and long-term success.